Rickettsiales 2016
DOI: 10.1007/978-3-319-46859-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of “Non-model” Rickettsiales and Their Association with Aquatic Organisms

Abstract: Representatives of the order Rickettsiales are obligate intracellular bacteria, traditionally including well-studied pathogens of humans and other vertebrates, such as Rickettsia, Orientia, Anaplasma, and Ehrlichia. In the last two decades, studies based on molecular characterization techniques have reshaped our view on the biodiversity of Rickettsiales, and the eukaryotic hosts they can exploit. Several new genera have been described in “traditional” Rickettsiales families Rickettsiaceae and Anaplasmataceae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 152 publications
7
31
0
Order By: Relevance
“…Midichloria is a genus of obligate intracellular bacteria belonging to the order Rickettsiales, a group of alphaproteobacteria composed by intracellular bacteria (with one exception; Castelli et al, ), which includes human pathogens (e.g. many Rickettsia species; Parola et al, ; Weinert, Werren, Aebi, Stone, & Jiggins, ), mutualists (Hosokawa, Koga, Kikuchi, Meng, & Fukatsu, ; Landmann, ; Taylor, Bandi, & Hoerauf, ), reproductive parasites (Werren, Baldo, & Clark, ) and a number of less‐studied lineages with unknown interactions with their host (Castelli, Sassera, & Petroni, ). Midichloriae have been found in several tick species, including I. ricinus (Beninati et al, ), Rhipicephalus bursa (Epis et al, ), Amblyomma maculatum (Budachetri et al, ), among others (Cafiso et al, ; Epis et al, ).…”
Section: Mitochondria An Emerging Target For Intracellular Bacteriamentioning
confidence: 99%
“…Midichloria is a genus of obligate intracellular bacteria belonging to the order Rickettsiales, a group of alphaproteobacteria composed by intracellular bacteria (with one exception; Castelli et al, ), which includes human pathogens (e.g. many Rickettsia species; Parola et al, ; Weinert, Werren, Aebi, Stone, & Jiggins, ), mutualists (Hosokawa, Koga, Kikuchi, Meng, & Fukatsu, ; Landmann, ; Taylor, Bandi, & Hoerauf, ), reproductive parasites (Werren, Baldo, & Clark, ) and a number of less‐studied lineages with unknown interactions with their host (Castelli, Sassera, & Petroni, ). Midichloriae have been found in several tick species, including I. ricinus (Beninati et al, ), Rhipicephalus bursa (Epis et al, ), Amblyomma maculatum (Budachetri et al, ), among others (Cafiso et al, ; Epis et al, ).…”
Section: Mitochondria An Emerging Target For Intracellular Bacteriamentioning
confidence: 99%
“…In the last two decades, many new genera and species of Rickettsiales were found as symbionts in a variety of other non-vector eukaryotic hosts, both from terrestrial and aquatic environments [reviewed in 3, 4, 7]. In particular, numerous such novel bacterial species were retrieved in aquatic protists [1822], including, notably, parasitic ( Ichthyophthirius multifiliis ) [23, 24] and various free-living ciliates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases the relationships between Rickettsiales associated with aquatic eukaryotes and their hosts were not clarified in detail, as in general no evident effect on host biology was observed [7], with the exception of “ Candidatus ( Ca .) Xenohaliotis californiensis”, which is considered the cause of the withering syndrome in its abalone hosts [41, 42].…”
Section: Introductionmentioning
confidence: 99%
“…Obligate intracellularity indeed represents the main feature of this bacterial order, considering that their host range, metabolic capabilities, and spectrum of effects on the hosts greatly vary (Perlman et al 2006;Werren et al 2008;Montagna et al 2013;Castelli et al 2016). As a matter of fact, Rickettsiales encompass highly diverse representatives, including human pathogens (Kocan et al 2004;Parola et al 2013;Weinert et al 2009), reproductive parasites of arthropods (Werren et al 2008), mutualists of nematodes (Taylor et al 2005;Werren et al 2008) or arthropods (Hosokawa et al 2010), and several bacteria associated with unicellular eukaryotes, producing undisclosed consequences on their hosts (Castelli et al 2016). Additionally, Rickettsiales are well known to evolutionary biologists, since several studies suggested them as the sister group of mitochondria (Andersson et al 1998;Fitzpatrick et al 2006;Wang and Wu 2015), although there is no full agreement on this point Abhishek et al 2011;Thiergart et al 2012;Martijn et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, such characteristics were instrumental in the parallel evolution of multiple strictly intracellular lineages within the order. Considering that most Rickettsiales (including Deianiraea) are found in aquatic environments(Castelli et al 2016) (Figure 5), the Proto-Rickettsiales was probably an aquatic bacterium as well(Vannini et al 2005;Ogata et al 2006; Weinert et al 2009;Driscoll et al 2013;Schrallhammer et al 2013;Kang et al 2014). Combining multiple features present in different Rickettsiales lineages, it is possible to infer that such Proto-Rickettsiales bacterium probably had a rather high metabolic and functional…”
mentioning
confidence: 99%